Classroom Ideas for Promoting Social Justice: Encouraging Student Activism in Intercultural and Gender Communication Courses - Amy Aldridge Sanford (Central States Communication Association, 2018)
Communication courses (e.g., intercultural communication and gender communication) dedicated to the promotion of social justice often result in students' raised consciousness regarding privilege and the oppression of people who have been marginalized historically. Affected students, however, often are at a loss about what to do with the newly acquired knowledge; consequently, they may experience anger and frustration that causes them to feel overwhelmed and leaves them with a sense of hopelessness. This essay provides 10 suggestions to help communication pedagogues guide students from anger and hopelessness to action and empowerment. Tips offered center on classroom discourse, curriculum choices, and potential assignments. DOI